2017
DOI: 10.1371/journal.pone.0175254
|View full text |Cite
|
Sign up to set email alerts
|

Soluble membrane receptors, interleukin 6, procalcitonin and C reactive protein as prognostic markers in patients with severe sepsis and septic shock

Abstract: BackgroundThe objective of this study was to explore the diagnostic and prognostic value of soluble triggering receptor expressed on myeloid cell 1 (sTREM-1), soluble cluster of differentiation 14 (sCD14), soluble cluster of differentiation 163 (sCD163), interleukin-6 (IL-6), procalcitonin (PCT), and C-reactive protein (CRP) serum levels for patients with severe sepsis and septic shock in an intensive care unit (ICU).MethodsFifty patients admitted at the ICU with the diagnosis of severe sepsis or septic shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 60 publications
4
54
1
1
Order By: Relevance
“…An increase in presepsin was also noted in AKI patients without sepsis, in line with the finding of Miyoshi and co-workers [89]. It is important to ensure that the correct analytical target is measured; one study described the use of presepsin, but closer inspection revealed that they had actually measured soluble CD14 and not presepsin (soluble CD14 subtype) [90].…”
Section: Adults Icusupporting
confidence: 75%
See 1 more Smart Citation
“…An increase in presepsin was also noted in AKI patients without sepsis, in line with the finding of Miyoshi and co-workers [89]. It is important to ensure that the correct analytical target is measured; one study described the use of presepsin, but closer inspection revealed that they had actually measured soluble CD14 and not presepsin (soluble CD14 subtype) [90].…”
Section: Adults Icusupporting
confidence: 75%
“…Comparison of sTREM-1 to PCT and CRP for diagnosis of sepsis has been performed, with results suggesting that sTREM-1 may have better performance (AUCs 0.82, 0.77 and 0.72 for sTREM-1, PCT and CRP, respectively) [106]. The authors also hinted at a possible prognostic role for sTREM-1, noting that concentrations were significantly higher in non-survivors compared to survivors, which was corroborated by other work [75,90,103]. In addition to its predictive value, its potential superiority to PCT and CRP was demonstrated by Brenner and co-workers [103].…”
Section: Adults Icusupporting
confidence: 59%
“…[21][22][23][24][25] The results showed the diagnosis accuracy and specificity of PCT are higher than those of CRP, and both of them have a moderate degree of diagnostic value. Currently, blood culture is the gold standard in the diagnosis of sepsis, but there are some restrictions such as poor sensitivity and longer inspection time.…”
Section: Discussionmentioning
confidence: 99%
“…After obtaining and thorough reviewing the full manuscripts, it was concluded that 58 articles did not meet the inclusion criteria because there were no outcomes or data deficiency (13), subjects were newborn (16), unqualified grouping (21), and unqualified content (8). After obtaining and thorough reviewing the full manuscripts, it was concluded that 58 articles did not meet the inclusion criteria because there were no outcomes or data deficiency (13), subjects were newborn (16), unqualified grouping (21), and unqualified content (8).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The CRP test is commonly used to indicate the presence of inflammation in many diseases. Many studies have confirmed its sensitivity in demonstrating inflammation after surgery [26–28]. Until now, there is no solid evidence to support its use before surgery, and none of the previous studies investigated its role in urolithiasis diseases.…”
Section: Discussionmentioning
confidence: 99%